2020
DOI: 10.3389/fneur.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Normobaric Hyperoxia Brain Protection in Experimental Stroke

Abstract: As we all know that stroke is still a leading cause of death and acquired disability. Etiological treatment and brain protection are equally important. This review aimed to summarize the advance of normobaric-hyperoxia (NBHO) on brain protection in the setting of experimental stroke and brain trauma. We analyzed the data from relevant studies published on PubMed Central (PMC) and EMBASE, about NBHO on brain protection in the setting of experimental ischemic and hemorrhagic strokes and brain trauma, which revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…As opposed to HBO, normobaric oxygen therapy (NBO) is high oxygen administration at normal pressure [ 35 ]. Despite both therapies diminishing hypoxic regions, at high pressures, it is possible to reach better oxygenation of the tumor [ 36 , 37 ].…”
Section: Impact Of Hyperoxia On Different Cancer Therapiesmentioning
confidence: 99%
“…As opposed to HBO, normobaric oxygen therapy (NBO) is high oxygen administration at normal pressure [ 35 ]. Despite both therapies diminishing hypoxic regions, at high pressures, it is possible to reach better oxygenation of the tumor [ 36 , 37 ].…”
Section: Impact Of Hyperoxia On Different Cancer Therapiesmentioning
confidence: 99%
“…The author believed that this may be the reason why TEER in the HBO-PC group was higher than that in the hypoxia group. Chen et al found that hyperoxia could reduce damage to the BBB, attenuate brain cell edema, lower intracranial pressure, improve cerebral blood flow, especially around areas of brain damage, and activate neurons in hemispheric areas(Chen et al 2020 ). These results demonstrated that HBO has the potential to protect the integrity of the BBB but need to be further validated.…”
Section: Potential Mechanism Of Hbo-pc For Ismentioning
confidence: 99%
“…84 Advances in normobaric hyperoxia application, particularly derived from animal studies evaluating effects in experimental stroke and brain trauma, have recently been reviewed. 85 While normobaric hyperoxia is commonly used in the settings mentioned above, the use of hyperbaric O 2 therapy seems to be more effective in other circumstances, for example, acute severe traumatic brain injury, 86 or carbon monoxide poisoning. 87 Noteworthy in this context, in severe burns, beneficial effects of hyperbaric O 2 therapy may include the attenuation of central sensitization.…”
Section: Exploiting O Manipulations For Improving Brain Function: Eff...mentioning
confidence: 99%
“…96,98,99 Moreover, underlying molecular mechanisms include variable changes in the expression of caspase-3, matrix metalloproteinase-9, aquaporin-4, and Na+/H+ exchanger-1. 85,100,101 On the other hand, contrasting effects of hypoxia versus hyperoxia were found, for example, in a mouse model of Friedreich's ataxia where breathing of 11% O 2 attenuated the progression of ataxia, whereas breathing 55% O 2 hastened it. 102 Effects of hypoxia versus hyperoxia on gene expression and functional or structural neuroplasticity have not been studied yet systematically and back-to-back.…”
Section: Exploiting O Manipulations For Improving Brain Function: Eff...mentioning
confidence: 99%